鐵之狂傲

標題: 挑戰23 [列印本頁]

作者: M.N.M.    時間: 06-4-2 05:51
標題: 挑戰23
1.設f(x)=(x+2)^4-8(x+2)^3+22(x+2)^2-24(x+2)+11,求f(5)=?

2.以13^2+13+1除13^85+13^25-8x13^10-4x13^2+8的餘數為何?

3.求(3x^2+2x-1)除f(x)=[(6x^2+4x-3)^13]+x+4之餘式為何?
作者: 飛天神劍    時間: 06-4-2 14:03
標題: 回覆: 挑戰23
1.f(5)=7^4-8*7^3+22*7^2-24*7+11
        =2401-2744+1078-168+11
        =578
作者: shalem    時間: 06-4-3 22:56
標題: 回覆: 挑戰23
3.
把3x^2+2x-1變成3x^2 = -2x + 1 (再同乘2)
得到 6x^2 = -4x + 2
=>[(6x^2+4x-3)^13]+x+4 (取代)
得[(-4x + 2 + 4x - 3)^13]+ x + 4
=> [(-1)^13]+ x + 4
=> (-1) + x + 4
=> x + 3
作者: M.N.M.    時間: 06-4-11 10:11
標題: 回覆: 挑戰23
[解答]
1.
令y=x+2=>y-2=x
(x+2)^4-8(x+2)^3+22(x+2)^2-24(x+2)+11
=y^4+-8y^2+22y^2-24y+11
=(y-2)^4-2(y-2)^2+3
=x^4-2x^2+3
f(5)=5^4-2*5^2+3=578

2.
令x=13,則原題變為求x^2+x+1除x^85+x^25-8x^10-4x^2+8之餘式
令x^2+x+1=0
=>x^3=1

x^85+x^25-8x^10-4x^2+8
=(x^3-1)Q(x)+x+x-8x-4x^2+8
=(x^3-1)Q(x)-4x^2-6x+8
=(x^3-1)Q(x)-4(x^2+x+1)-2x+12

所以餘式為-2x+12,即-2*13+12=-14
但由原題得知不可能為負
所以-14+(13^2+13+1)=169

3.shalem已解出




歡迎光臨 鐵之狂傲 (https://gamez.com.tw/)